What Makes a Face-Saving Leadership Style: The Dual Effects of Uncertainty Avoidance and Power Distance Cultural Values - Hidajat Hendarsjah; Mulyadi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The self-protective leadership style (SPL) prioritizes the safety and security of the leader and the group while focusing on maintaining status and avoiding mistakes. In this leadership style, leaders may focus on face-saving behavior, maintaining their position, and avoiding making bold decisions that could lead to failure. Amid the controversy, this perspective raises further questions about what factors drive the formation of this leadership style. On the other hand, cultures that value uncertainty avoidance may be more likely to support self-protective leadership because of (1) the need for stability: people in these cultures may prefer leaders who prioritize stability and security over innovation or taking chances; this may result in leaders who are cautious and avoid making risky decisions, and (2) a focus on rules: clear rules and structures are important in high uncertainty avoidance cultures, so leaders who follow established procedures may be perceived as more reliable. Purpose: This study focused on elaborating the dual effects of cultural values of Uncertainty Avoidance and Power Distance cultural values in shaping the face-saving attitude dimension of self-protective leadership. Design/methodology/approach: GLOBE Project data at the country level were used to elaborate on the phenomenon. The study used multivariate analysis that elaborated on the moderating role of the regression technique. To further test the assumption of Power Distance as a moderator, a series of further regression tests was conducted to see whether the Power Distance variable was confirmed as a moderator. The simple slope analysis technique was used to observe characteristics of the moderating role of Power Distance on the associative relationship between Uncertainty Avoidance and Face-Saver.  Findings/Results: The findings showed that Uncertainty Avoidance had a positive relationship with the formation of the face-saving dimension of SPL. At the same time, the expected contextual factor of Power Distance did not influence the strength of the positive association between Uncertainty Avoidance and Face-Saver; instead, it had a dual effect with Uncertainty Avoidance in forming the Face-Saver orientation. Conclusion: The findings implied the possibility of trickiness in obtaining the effective leadership practices, which could be dominated by the Face-Saver orientation when high Uncertainty Avoidance and high Power Distance cultural values exist.Originality/Value (State of The Art): The results of this study indicate that reducing Power Distance orientation can reduce the formation of Face-saver characteristics in organizations. Future research must test whether the presence of a flat structure and cross-functional teams can reduce the formation of face-saving practices in organizations.  Keywords: face-saver, leadership, uncertainty avoidance, power distance, self-protective leadership